Secondary atomization of water-in-oil emulsion drops impinging on a heated surface in the film boiling regime; International Journal of Heat and Mass Transfer; Vol. 165, Pt. B - Piskunov M. V. Maksim Vladimirovich; Breitenbach J. Jan; Schmidt J. B. Benedikt; Strizhak P. A. Pavel Alexandrovich; Tropea C. Cameron; Roisman I. V. Ilia (2021, 2021)
Title screen